O38 Military simulation training for the austere environment. (5th November 2017) - Fadden, SJ; Clitheroe, EC; Hall, BGR; Jones, CP
Abstract : Context: Military operations in austere environments necessitate the deployment of teams that are characteristically small and mobile, with comparable medical support. To offset the inevitable resource limitations, these medical teams must be able to deliver judicious care, promptly and appropriately, using well-rehearsed clinical skills, uncomplicated treatment protocols and rationalised, portable, equipment. The Military Medics course at the Centre for Simulation and Patient Safety, Aintree University Hospital, is designed to provide immersive small team training that replicates the practical, logistical and situational challenges of the operational environment. The course has evolved to maximise fidelity and elicit specific technical and non-technical skills. Methodology: Candidates on the Military Medics course undertake multiple high-intensity simulation training scenarios. Teams comprising two medics and a general practitioner are exposed to a variety of simulations, dealing with both trauma and medical patients, set in different pre-hospital environments. Although the training is delivered in a standard simulation suite, using mannequin casualties, scenario fidelity is enhanced by simple strategies, including: 1. Utilisation of authentic military medical kit and Standard Operating Procedures (SOPs). 2. Staging of audio-visual effects – gun fire, helicopter noise, reduced (red) light and diminished working space. 3. Replication of military medical logistics in terms of communication (using radios) and processes (escalation of clinical management via telemedicine). The learning objectives for each scenario focus on human factors and crew resource management. Technical and non-technical skills are identified collaboratively, with the assistance of video playback, and debriefed by subject-matter experts. Lectures/workshops on specific topics augment the multimodal learning experience. Outcomes: Candidate feedback is used as the primary means of evaluating the Military Medics course. This has led to the course being extended from three to five days in order to increase the number and complexity of scenarios delivered. Candidates have remarked that the course is particularly useful for exposing latent errors with SOPs and equipment. Candidates have suggested increasing the amount of technical pre-course reading material, and have identified decision-making and crew resource management as valuable non-technical skills promoted by the course. Conclusion: The Military Medics course provides a high fidelity, fully immersive, simulation training experience. A future aspiration is to deliver the course in a military establishment, although one with a dedicated simulation facility would be most effective. By focusing on small teams and human factors, the Military Medics course facilitates the development of cohesive medical units that are capable of deploying to resource-limited austere environments.